Analysis of Mechanical and Magnetic Properties of Rubber Magnet Composite Made From NdFeB Magnetic Particlesand Silicon Rubber - Edi Tri Astuti; Mulyadi Mulyadi; Sunardi Sunardi; Joko Setiyono (Piston: Journal of Technical Engineering, 2023)
This study conducted the manufacture of permanent magnet composite based on NdFeB magnetic powder and polymer adhesives, the purpose of this study was to determine the effect of the composition of the mixing of raw materials on mechanical properties and magnetic properties. Neodymium Iron Boron (NdFeB) composite was made by mixing of NdFeB magnetic powder and binder of silicon rubber (SR) in form liquid. The percentage of silicon rubber was varried of 5 %, 10%, 20 % and 30% by volume. Both raw materials were mixed until homogeneous and poured into the mold and allowed to dry at room temperature.The formed samples were characterized which includes the measurement of tensile strength and magnetic properties . The characterization results show that the sample with 20 % and 30 % SR has good flexibilty and other samples are rigid or not flexible. The variation in the composition of silicon rubber has a significant effect on mechanical properties and magnetic properties, especially remanence. The characteristic of flexible rubber magnet with a composition of 20% and 30% silicon rubber is that it has a tensile strength of 9.31 - 11.46 N / mm2 with an elongation of 17.55-26.74% and a hardness of 38-42 HA. While the magnetic properties achieved are magnetic field strength = 430-500 Gauss, remanence = 30-35 emu / g and coercivity of 2000 Oe